2010
DOI: 10.1111/j.1365-2125.2010.03811.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐related differences in hospital admissions attributed to adverse drug reactions in the Netherlands

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECTWomen are more at risk for developing adverse drug reactions (ADRs) due to differences in pharmacokinetics, pharmacodynamics and drug use. ADRs regularly lead to hospital admissions. WHAT THIS STUDY ADDSThere are differences between the sexes in hospital admissions attributed to ADRs. The risk of being hospitalized with an ADR varies between the sexes in the type of reaction and the causative drug. AIMAdverse drug reactions (ADRs) are a major burden in health care, regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 42 publications
7
48
3
2
Order By: Relevance
“…117 Side effects of antihypertensive therapy tend to be encountered with a higher degree of frequency in women than men. Diuretic-induced disturbances of electrolyte concentration are seen more frequently in women, 118,119 as is angiotensinconverting enzyme inhibitor-induced cough and calcium channel blocker (CCB)-related dependent edema.…”
Section: Sex Bp Antihypertensive Treatment and Achieving Bp Goalsmentioning
confidence: 99%
“…117 Side effects of antihypertensive therapy tend to be encountered with a higher degree of frequency in women than men. Diuretic-induced disturbances of electrolyte concentration are seen more frequently in women, 118,119 as is angiotensinconverting enzyme inhibitor-induced cough and calcium channel blocker (CCB)-related dependent edema.…”
Section: Sex Bp Antihypertensive Treatment and Achieving Bp Goalsmentioning
confidence: 99%
“…Epidemiologic studies in large population samples have shown an increased risk of adverse drug effects among females 31,32 however, most MDA dosages in LF elimination programs have been defined based on population parameters of weight-for-age 13,14,33,34 and have not considered sex variations in weight in terms of the tolerability of antifilarial drugs. The data from this study suggest that adjusting dosage schedules in MDA by genders may reduce the occurrence of ADRs, primarily by reducing the number of ADRs in the female population.…”
Section: Discussionmentioning
confidence: 99%
“…Both frequency and character of ADE in women may depend on the drug type (Rodenburg et al 2011). For example, iatrogenic osteoporosis and fractures can be induced by corticosteroids, thiazolidinedione, and aromatase inhibitors.…”
Section: Females' Vulnerability Respect To Specific Classes Of Drugsmentioning
confidence: 99%